Spatial distribution of the chromosomal forms of anopheles gambiae in Mali - Sogoba, Nafomon (BioMed Central, 2008)
BACKGROUND: Maps of the distribution of malaria vectors are useful tools for stratification of malaria risk and for selective vector control strategies. Although the distribution of members of the Anopheles gambiae complex is well documented in Africa, a continuous map of the spatial distribution of the chromosomal forms of An. gambiae s.s. is not yet available at country level to support control efforts. METHODS: Bayesian geostatistical methods were used to produce continuous maps of the spatial distribution of the chromosomal forms of An. gambiae s.s. (Mopti, Bamako, Savanna and their hybrids/recombinants) based on their relative frequencies in relation to climatic and environmental factors in Mali. RESULTS: The maps clearly show that each chromosomal form favours a particular defined eco-climatic zone. The Mopti form prefers the dryer northern Savanna and Sahel and the flooded/irrigated areas of the inner delta of the Niger River. The Savanna form favours the Sudan savanna areas, particularly the South and South-Eastern parts of the country (Kayes and Sikasso regions). The Bamako form has a strong preference for specific environmental conditions and it is confined to the Sudan savanna areas around urban Bamako and the Western part of Sikasso region. The hybrids/recombinants favour the Western part of the country (Kayes region) bordering the Republic of Guinea Conakry. CONCLUSION: The maps provide valuable information for selective vector control in Mali (insecticide resistance management) and may serve as a decision support tool for the basis for future malaria control strategies including genetically manipulated mosquitoes.